Iraq in wartime : soldiering, martyrdom, and remembrance - Khoury, Dina Rizk. (Cambridge : Cambridge University Press, 2013)
"When US-led forces invaded Iraq in 2003, they occupied a country that had been at war for 23 years. Yet in their attempts to understand Iraqi society and history, few policy makers, analysts and journalists took into account the profound impact that Iraq's long engagement with war had on the Iraqis' everyday engagement with politics, the business of managing their daily lives, and their cultural imagination. Drawing on government documents and interviews, Dina Rizk Khoury traces the political, social and cultural processes of the normalization of war in Iraq during the last twenty-three years of Ba'thist rule. Khoury argues that war was a form of everyday bureaucratic governance and examines the Iraqi government's policies of creating consent, managing resistance and religious diversity, and shaping public culture. Coming on the tenth anniversary of the US-led invasion of Iraq, this book tells a multilayered story of a society in which war has become the norm"--
Machine generated contents note: 1. Introduction; 2. A brief history of Iraq's wars under the Ba'th; 3. The internal front: making the war routine; 4. Battle fronts: war and insurgency; 5. Things fall apart: the First Gulf War and its aftermath; 6. War's citizens, war's families; 7. Memory for the future: soldiering and the war experience; 8. Commemorating the dead; 9. Postscript.
Includes bibliographical references (pages 261-270) and index.
Keywords: Politics and war -- Iraq -- History -- 20th century; War and society -- Iraq -- History -- 20th century; Iran-Iraq War, 1980-1988 -- Political aspects -- Iraq; Iran-Iraq War, 1980-1988 -- Social aspects -- Iraq; Persian Gulf War, 1991 -- Political aspects -- Iraq; Persian Gulf War, 1991 -- Social aspects -- Iraq; Iraq -- Politics and government -- 1979-1991.